WHISTLEBLOWING (ERDEMLİ RAPORLAMA) VE MANTAR YÖNETİM ARASINDAKİ İLİŞKİ - Çetinkaya, Fatih Ferhat; Altıntaş, Mustafa (Fırat University, 2021)
Management forms are always determined as a topic of research for organizations. The concept of mushroom management that has been on the agenda in recent years, is a management style that researchers are interested in. Mushroom management is a management style in which most of the information is not shared with employees. Incontrary; the concept of whistleblowing is the transmission of useful information which is perceived positively in terms of organization to the administration by the employees, The study was considered as important in terms of revealing how whistleblowing behavior changes in organizations which has different management styles. The aim of the research is to reveal whether mushroom management has an effect on whistleblowing and its sub-dimensions. The study was conducted on 470 private sector employees. The data collected with the survey technique were subjected to the necessary statistical analysis. As a result of the research, it has been determined that mushroom management has no effect on whistleblowing behavior. As a result of the research, additionally it was determined that mushroom management positively and significantly affected external whistleblowing which is one of the sub-dimensions of whistleblowing, but it is also determined that the mushroom management affected internal whistleblowing negatively and significantly and affected in difference negatively and significantly. In the light of these results, it has been tried to contribute to the relevant literature.

Yönetim şekilleri örgütler açısından her zaman araştırma konusu yapılmaktadır. Son yıllarda gündemde olan mantar yönetim kavramı da araştırmacıların ilgilendiği bir yönetim tarzıdır. Mantar yönetim çalışanlar ile çoğu bilgilerin paylaşılmadığı bir yönetim şeklidir. Whistleblowing kavramı ise çoğu zaman örgütsel açıdan pozitif bir şekilde algılanan örgüte faydalı bilgilerin çalışanlar tarafından yönetime iletilmesidir. Farklı yönetim tarzlarının olduğu örgütlerde erdemli raporlama davranışının nasıl değişikli gösterdiğinin ortaya konulması açısından çalışma önemli görülmüştür. Araştırmanın amacı, mantar yönetimin erdemli raporlamaya ve alt boyutlarına etkisi olup olmadığını ortaya koymaktır. Çalışma 470 özel sektör çalışanı üzerinde yapılmıştır. Anket tekniği ile toplanan veriler gerekli istatistiki analizlere tabi tutulmuştur. Araştırma sonucunda, mantar yönetimin erdemli raporlama davranışına etkisinin olmadığı tespit edilmiştir. Yine araştırma neticesinde mantar yönetimin erdemli raporlamanın alt boyutlarından olan dışsal erdemli raporlamayı pozitif ve anlamlı şekilde etkilediği, mantar yönetimin içsel erdemli raporlamayı negatif ve anlamlı şekilde etkilediği ve mantar yönetimin kayıtsızlığı negatif ve anlamlı şekilde etkilediği tespit edilmiştir. Bu sonuçlar ışığında ilgili literatüre katkı sağlamaya çalışılmıştır.
WHISTLEBLOWING (ERDEMLİ RAPORLAMA) VE MANTAR YÖNETİM ARASINDAKİ İLİŞKİ